16 years of e-Justice in Brazil: a literature review - Rocha, Cinara M.C. (2023)
Since 2006, with the enactment of the "Law of Electronic Judicial Proceeding", Brazil has been consistently transforming its Justice System by migrating from paper to a digital-based process. Currently, 97% of lawsuits are digital. This study performs a literature review of 29 papers addressing the Brazilian Electronic Judicial Process (EJP). First, we point out the steps taken during EJP deployment. Then we classify the studies based on Delone and MacLean's Information System Success Model, contributing to systematically organising the knowledge. The research demonstrates the importance of the normative framework enabling the EJP and the National Council of Justice's essential role in driving the digital transformation of the Justice System in Brazil. Papers related to the assessment of the EJP are fragmented, of different natures, and address a wide range of aspects, not allowing consistent conclusions about the overall success of EJP.